An international comparison of the causes of changes in the debt service ratio 1980-1985 - GIBSON, H.D.; THIRLWALL, A.P. (PSL Quarterly Review, 2013)
The forces leading up to the debt crisis of the 1980s go back a long way. As a country experiences a rising ratio of debt service payments to export earnings so its default risk increases. World indicators show that interest rates were on a rising trend when commodity prices were on a downward trend. However, this is a simplistic analysis. The authors disaggregate the ratio into five components: a change in the volume of debt; a change in the rate of amortisation; a change in the rate of interest; a change in the volume of exports; a change in the price of exports. The article examines these independently in the light of the available data. Results suggest that rescheduling policy is uncoordinated and that debt-management methods can be improved. JEL: F34, H63, E43